Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0719
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Education Programs and Procedures

Abstract: Olszewski‐Kubilius reviews work focused on defining characteristics of gifted children as well as on demonstrating important implications for education. Key research is presented to support the striking capabilities of gifted children and the increasing evidence of the stability of exceptional abilities. Considerable evidence is presented on inter‐ and intra‐individual variance, asynchronous development, and distinct ability profiles. Difficulties associated with current definitions of giftedness and the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Problems with the identification and recruitment methods used to solicit students for gifted education are frequently cited as major contributing factors to the underrepresentation of low-income and minority students (Olszewski-Kubilius & Thomson, 2003). Research has found that traditional intelligence tests, such as the Wechsler Intelligence Scale for Children–Fourth Edition (WISC-IV; Wechsler, 2003), have yielded lower scores for minority children (Naglieri & Ford, 2003).…”
Section: Recruitment and Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Problems with the identification and recruitment methods used to solicit students for gifted education are frequently cited as major contributing factors to the underrepresentation of low-income and minority students (Olszewski-Kubilius & Thomson, 2003). Research has found that traditional intelligence tests, such as the Wechsler Intelligence Scale for Children–Fourth Edition (WISC-IV; Wechsler, 2003), have yielded lower scores for minority children (Naglieri & Ford, 2003).…”
Section: Recruitment and Identificationmentioning
confidence: 99%
“…In addition to the measures specifically designed as nonverbal assessments, practitioners have the option to choose from nonverbal indices built into traditional cognitive assessments, such as the mental processing index or the nonverbal index found on the Kaufman Assessment Battery for Children, Second Edition (KABC-II; Kaufman & Kaufman, 2004) or the nonverbal index found on the Wechsler Intelligence Scale for Children–Fifth Edition (WISC-V; Wechsler, 2014). These nonverbal tests have been deemed more culturally sensitive because they place greater emphasis on fluid reasoning ability, which relies less on language and academically acquired knowledge (Naglieri & Ford, 2003; Olszewski-Kubilius & Thomson, 2003).…”
Section: Recruitment and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of enhanced scientific and public efforts to improve gifted education in the last decades -numerous measures and programs to promote gifted students have been developed and documented worldwide since the 1980s (Heller & Perleth, 2007;Olszewski-Kubilius, 2003;Preckel & Vock, 2013;Shavinina, 2009) -there evidently are still a lot of difficulties to implement some of these measures in the daily routine of German schools. Even the intensified discussion on inclusion recently led in German educational policy mostly ignores gifted children and efforts to implement inclusion in German classrooms are mostly restricted to children with handicaps or learning disabilities (Boban & Hinz, 2013;Heimlich & Kahlert, 2014; see also Vogt & Krenig, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the successful programs in gifted education that have been developed in the last years combine elements of acceleration and enrichment, the two basic principles of differentiation frequently applied in programs for gifted students as well as in measures for individualized differentiation (Olszewski-Kubilius, 2003). Acceleration means that students pass the normal curriculum faster than their peers.…”
Section: Introductionmentioning
confidence: 99%